Hemoperfusion with Cytosorb in pediatric patients with septic shock: A retrospective observational study. Issue 9 (September 2020) - Bottari, Gabriella; Guzzo, Isabella; Marano, Marco; Stoppa, Francesca; Ravà, Lucilla; Di Nardo, Matteo; Cecchetti, Corrado
Objective: To determine the clinical effect of continuous hemoperfusion with Cytosorb associated with standard Continuous Renal Replacement Therapy on hemodynamics and on clinically relevant outcome parameters in children with septic shock. Design: Retrospective analysis. Setting: Pediatric intensive care unit. Patients: Eight consecutive children with septic shock who received hemoperfusion with Cytosorb while on Continuous Renal Replacement Therapy. Interventions: Continuous hemoperfusion with Cytosorb (adsorber was changed every 24 h). Measurements and main results: Vasoactive-Inotropic Score was measured before and after the extracorporeal blood purification treatment. Bedside refractory septic shock score was calculated before the onset of the extracorporeal blood purification treatment. Time course of cytokines interleukin-6, interleukin-10, and tumor necrosis factor–alpha was measured at Time 0, then every 12 h until the end of blood purification treatment (72 or 96 h). Pediatric intensive care unit survival in our cohort was 90%. Median bedside refractory septic shock score was 2.1. Patients showed improved Vasoactive-Inotropic Score following blood purification (pre: 40.00 post: 8.89 p  = 0.0076). Measurement of cytokines level showed a significant reduction of interleukin-6 plasma levels (7977.27–210.18 pg/mL, p  = 0.0077) and interleukin-10 plasma levels (from 687.19 to 36.95 pg/mL, p  = 0.0180). In those patients with detectable tumor necrosis factor–alpha plasma level, its reduction was not significant ( p  = 0.138). The median removal ratio was 80% for interleukin-6, 90% for interleukin-10, and 29% for tumor necrosis factor–alpha. Conclusion: The use of Cytosorb in combination with Continuous Renal Replacement Therapy as blood purification strategy in pediatric septic shock is associated with a rapid hemodynamic stabilization in the first 48 h of treatment and a significant reduction of interleukin-6 and interleukin-10.